Veer e midir. The licensing of private building works in Lisbon in the modern period - Pinto, Sandra M. G. (Cuadernos de Historia del Derecho, 2016)
Using legal instruments and council records, this article analyses the legal rules, the procedure and the cost of licensing a private building work as well the practices used by competent authorities to sanction and solve illegal actions in Lisbon through the modern age.
Keywords: Licensing; private building; legal norms; procedure; modern period; Lisbon; Portugal